Sodium vanadium oxide : a new material for high-performance symmetric sodium-ion batteries - Hartung, Steffen (2014)
Room-temperature sodium-ion batteries have the potential to become the technology of choice for large-scale electrochemical energy storage because of the high sodium abundance and low costs. However, not many materials meet the performance requirements for practical applications. Here, we report a novel sodium-ion battery electrode material, Na2.55V6O16⋅0.6 H2O, that shows significant capacities and stabilities at high current rates up to 800 mA g−1. X-ray photoelectron spectroscopy measurements are carried out to better understand the underlying reactions. Moreover, due to the different oxidation states of vanadium, this material can also be employed in a symmetric full cell, which would decrease production costs even further. For these full cells, capacity and stability tests are conducted using various cathode:anode mass ratios.